Use of therapeutic offices involving reading and dynamics as proposals for multiprofessional action in CAPS - Vanessa Domingos de Morais; Miriam Cristina Leite Felix; Sônia Maria Alencar Lima; Maria Jaidete Jó Alves (Tempus – Actas de Saúde Coletiva, 2024)
In view of the reformulation of the care model proposed by the psychiatric reform, the Psychosocial Care Centers (CAPS) were created through a multiprofessional team to offer therapeutic activities aimed at the construction of new ways of caring for the user with mental disorder. The realization of therapeutic workshops allows the possibility of expressing feelings in a healthy and creative way, stimulating self-esteem and self-confidence. This work is a descriptive study in the experience reporting modality, based on the activities developed by residents of nursing, pharmacy and nutrition in the therapeutic workshops held at CAPS Walk in the city of João Pessoa / PB. The aim of this work was to promote access to knowledge, exchange of ideas and cultural production through the reading of poetry and cords, use of music and dynamics. Therapeutic workshops were used weekly, in which an average of 35 users participated. At each meeting we realized the importance of CAPS and therapeutic workshops in the production of care not only for them, but also for their families. It is concluded that the realization of the therapeutic workshops are enriching spaces for providing links between users, families and CAPS staff, thus allowing both the family and the patient to reorganize their routine and also to return their activities in society.